Tlallamiquiliztli inelhuayo - Martínez Rosas, Crispín (University of Warsaw Press, 2025)
Tlallamiquiliztli inelhuayo is a novel in the Nahuatl language written by Crispín Martínez Rosas, an Indigenous author from a Nahua community in the Mexican state of Veracruz. Enriched with descriptions of local customs and beliefs, it immerses us in the reality of the inhabitants of a small, Native village engaged in a dispute over land with Church and government-backed paramilitary forces in the 1970s.